The quality of life of people with spinal cord injury - Stocka, Joanna; Simińska, Joanna; Ratuszek-Sadowska, Dorota; Miszewska, Agnieszka; Świątkowska, Anna; Głowacka-Mrotek, Iwona; Nowacka, Krystyna; Hagner, Wojciech (Journal of Education, Health and Sport, 2018)
Spinal injuries are the most common cause of formation of spinal subsequently they may be formed as a result of inflammation, tumors or other diseases. Among the consequences of spinal cord injury can be distinguished numbness, paralysis or paresis as well as restrictions within the urinary tract and sexual performance. There is also the increased chance of bedsores. The appearance of abnormal muscle tone and spasticity in the form of periarticular ossification. These problems make it difficult to "normal" functioning in society. Rehabilitation for patients with spinal cord injury is aimed at reducing symptoms and finding methods that most effectively compensated by the quality of deficiencies in the functioning of society.